Assessment of land degradation neutrality to guide sustainable land management practices in Ethiopia - Mekuria, Wolde; Girma, R. (Elsevier, 2025)
Since its introduction at the 2015 UN Convention to Combat Desertification Conference, the concept of land degradation neutrality (LDN) has guided countries’ efforts to restore land for sustainable socio-economic and environmental benefits. LDN aims to balance reductions in land quality with initiatives to rehabilitate degraded land. However, due to budget constraints, it is not feasible to address all degraded land, necessitating strategic decisions about where to invest resources. This study, using Ethiopia as a case study, aimed to: (i) assess the long-term (1995 - 2024) land degradation trends, (ii) identify areas of net land loss or gain, (iii) prioritize regions and actions for addressing LDN, and (iv) evaluate the impact of Ethiopia’s landscape management initiatives on LDN. The analysis of LULC changes and the observed landscape transformation across diverse agroecological zones yielded mixed results. While some areas, such as the dry Kolla and dry Weyna Dega regions, showed improvement, others, including the dry Dega and der Berha zones, experienced continued degradation. These variations affected the three main objectives of LDN: healthy ecosystems, food security, and human well-being. The ongoing landscape transformation, driven by LULC changes, underscores the need for more comprehensive strategies to mitigate further degradation and restore affected lands. Our findings regarding LDN trajectories, such as a 6 % reduction in degraded land between 2010 and 2024, suggest that national LDN implementation, through diverse Sustainable Land Management (SLM) practices, is essential for achieving the country’s LDN goals. However, LDN outcomes varied across Ethiopia’s agroecological zones, influenced by differences in environmental conditions, land use practices, and socio-economic factors. This highlights the necessity for tailored solutions, an understanding of varying restoration potentials, targeted resource allocations, and a focus on prioritizing the most vulnerable areas. Additionally, documenting both the successes and challenges of Ethiopia’s restoration efforts, enhancing the effectiveness of its landscape management initiatives, and ensuring the long-term sustainability of its SLM practices are critical for achieving LDN.